2022
DOI: 10.6007/ijarafms/v12-i1/11813
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Islamic Financing on the Small Medium Enterprises (SME’s) Performance in Lasanod Somalia

Abstract: The objective of this paper is to examine the influence of Islamic financing on the performance of small-medium enterprises in Lasanod Somalia. Many businesses obtain financings such as Murabaha, Microfinance, and Qard Al Hassana from Islamic banks operating in Somalia to raise funds and capital required to expand and run their businesses smoothly. This study employs a quantitative research approach. A total of 148 questionnaires were distributed and collected from Small Medium Enterprises owners and workers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A report by FurtherAfrica, an online news platform, stated that almost 80% of Somalian people are unbanked (FurtherAfrica, 2022). Abdinur and Ondes (2022) distributed 148 questionnaires in their study on Islamic financing and small and medium enterprises (SMEs) in Somalia. Table 1 provides the overall breakdown of the sampled respondents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A report by FurtherAfrica, an online news platform, stated that almost 80% of Somalian people are unbanked (FurtherAfrica, 2022). Abdinur and Ondes (2022) distributed 148 questionnaires in their study on Islamic financing and small and medium enterprises (SMEs) in Somalia. Table 1 provides the overall breakdown of the sampled respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Musse et al (2019) reported that the main reasons why tawarruq is not offered in Somalia are insufficient human capital, low level of awareness of the product and Shariah issues pertaining to the product. So far, there are limited empirical studies that have been conducted in Somalia about Islamic banks, particularly tawarruq (Abdinur and Ondes, 2022). Therefore, this study aims to evaluate the possible application of tawarruq contract in Somalia for cash financing purpose by focusing on the various factors, following (Amin et al , 2014; Obeid and Kaabachi, 2016; Jansson, 2011; Nomran and Haron (2020); Amin et al , 2018; Chawla and Joshi, 2019; Musse et al , 2019; Haron et al , 2020) i.e.…”
Section: Background and Objectives Of The Studymentioning
confidence: 99%
“…Recent data and trends suggest that numerous MSEs in Mogadishu are grappling with underwhelming performance metrics. For instance, a preliminary survey conducted in 2022 indicated that over 60% of MSEs in the city reported stagnant or declining profits over the past year, while another 45% acknowledged facing significant challenges in penetrating or sustaining their market positions (Abdinur and Karcioglu, 2023). This declining trajectory of MSEs' performance is not merely a statistic but represents a dire concern for local entrepreneurs, investors, and the broader Mogadishu economic fabric.…”
Section: Problem Statementmentioning
confidence: 99%
“…Further, Abdinur and Karcioglu (2023) research also highlighted that effective handling of organizational and financial data in business management requires the utilization of highquality accounting information systems (AIS). However, most SMEs in Somalia have been sluggish to embrace such information systems.…”
Section: Literature Review Empirical Reviewmentioning
confidence: 99%
“…Recent studies concerning AIS within the tourism sector have emphasized the need for a more profound understanding of the challenges confronted during the implementation of these systems and the strategies formulated to overcome them (Abdinur & Karcioglu, 2023;Thuan et al, 2022;Elsharif, 2019). Nonetheless, a conspicuous gap persists in the literature, particularly focusing on tourism enterprises in Boac, Marinduque, and there is a conspicuous lack of focus on the impact of human error on financial reporting and decision-making in this context.…”
Section: Introductionmentioning
confidence: 99%